Arbitrabilidade nos contratos com a administração pública - Skitnevsky, Karin Hlavnicka (2008)
The following work concerns about arbitrability as a limitation of the institute of arbitration, as far as a national and international context are concerned, as well as discuss about the possibility of Public Administration enter into agreements with arbitral clauses and ultimately to take part into this institute of private law. Initially, it introduces the concept of arbitration and a brief out-line of said institute, intending to comprehend its origins, its development jointly with the process of globalization and the institute before and after the Brazilian Law of Arbitration n. 9.307/96, as well as the international conventions ratified by Brazil and the historical background of arbitration into the agreements involving the Public Administration. After we present the arbitrability concept and the limitations, as the public policy and the applicable principles and the method of utilization of such technique in countries such as United States, Switzerland and France and also the limits and application of arbitrability in accordance with Brazilian Arbitration Law. Nevertheless and furthermore, by means of an expository manner, to demonstrate as being possible the inclusion of arbitrability provisions in the public agreements and the possibility the State to become participant party in either international and nationals arbitrations, as well as existing limitations in the Brazilian Constitution and in the general principles of public law, and finally an analysis of the Public Administration legislation as to wether expressly or not set-forth the acceptability and usage of arbitration